Blazing New Trails: Strengthening Policy Research in Gifted Education. (July 2017) - Plucker, Jonathan A.; Makel, Matthew C.; Matthews, Michael S.; Peters, Scott J.; Rambo-Hernandez, Karen E.
Policy research in gifted education has occurred at much lower rates than other areas of research within the field, such as identification and talent development. However, without changes and implementation of these policies, systematic change is unlikely to occur. Therefore, the purpose of this article is to argue that policy research should be a top priority. To begin, we define and contrast three terms common in crafting policy—policy, advocacy, and intervention. Next, we provide a context of previous policy research in gifted education. We then detail areas in which policy research is the most critical. Finally, we conclude with action steps to engage more researchers and practitioners in policy development, implementation, and monitoring.